The role of social media in participation to control the COVID-19 pandemic - Aminian, Nasrin; Hashemi, Shahnaz; Soltanifar, Mohammad; Ghorbani, Fariba (Researcher Bulletin of Medical Sciences, 2025)
Objective: We aimed to assess the role of virtual media in people’s participation in controlling the COVID-19 pandemic. Materials and Methods: This cross-sectional study was conducted from January to March 2022 using a researcher-made questionnaire via a panel expert. Considering participation of 10 experts, according to Lawshe table, the minimum value of the CVR index of 0.62 and the minimum score of the CVI index of 0.79 were acceptable. The questionnaire included two parts of demographic data and the assessment of the use of social network and its effect on people’s participation to manage COVID-19 pandemic. The questionnaire was circulated, and all people were invited for participation. Results: The response rate was 58% and 468 participants with a mean age of 38.5 ± 11.5 years took part in this study of which 42.3% were male. The quality of the samples and data were suit for factor analysis, KMO index was more than 0.6 and the p-value (0.05) with Cronbach’s alpha (0.88.). So according to the highest factor loading, 7 factors including the level of knowledge, the role of non-interactive media for providing information regarding COVID19, the level of people’s participation regarding compliance with protocols, the role of the media and trust in the media, controlling the psychological burden of the disease, the role of the interactive media, the role of other sources of information. Conclusion: The confirmatory factor analysis revealed that this tool by 7 factors could assess the role of virtual media in people’s participation to control the COVID-19 pandemic.